Probiotic preserving extract supplementation as a novel attitude in managing diabetes mellitus - Afrooz Saadatzadeh; Seyed Mohammad Kazem Emamifar; Seyyed Ali Mard; Akram Ahangarpour; Kambiz Ahmadi Angali; Sanaz Mehdialamdarlou (BMC Complementary Medicine and Therapies)
Abstract Type 2 diabetes is a metabolic disease characterized by insulin resistance. This study evaluated the effects of oral supplementation with a lyophilized probiotic extract (LPE) of Lactobacillus acidophilus and Lactobacillus plantarum on insulin resistance and inflammation reduction in rats with diabetes induced by streptozocin and nicotinamide. To induce diabetes, a single intraperitoneal injection of streptozocin (90 mg/kg) was administered following a dose of nicotinamide (105 mg/kg). In this experimental study, 36 adult male rats were randomly divided into six groups: a negative control group, a sham group, a positive control group (treated with metformin), and three groups treated with varying doses of LPE (60, 120, and 240 mg/ml). The LPE and metformin supplements were given orally daily for two weeks. Blood samples were collected the day before the treatment began and on the 15th. Results showed that diabetes significantly increased levels of TNF-α (an inflammatory marker), fasting blood sugar (FBS), and insulin levels, and leading to increased insulin resistance across all groups. However, the parameters measured in the LPE-treated groups showed significant differences compared to the other groups (P < 0.05 in all cases). LPE supplementation improved insulin sensitivity in diabetic rats through its hypoglycemic and anti-inflammatory effects. Clinical trial number Not applicable.